Establishment of Community Managed Fisheries' Closures in Kenya: Early Evolution of the Tengefu Movement. Issue 1 (2nd January 2016) - McClanahan, Tim; Muthiga, Nyawira A.; Abunge, Caroline A.
Abstract: Community-based management (CBM) could be an essential tool to prevent the depletion of marine resources in the Western Indian Ocean region. In Kenya, political pressure to strengthen local governance, has led to adoption of CBM as a way of reducing over-exploitation and managing the competing uses and impacts on the marine environment. Several communities in Kenya have embraced CBM and have set aside or closed previously fished areas to enhance recovery of fisheries and biodiversity. These community fisheries closures (locally called tengefu), despite being degraded, may recover to finfish abundances and biodiversity levels similar to established MPAs or above thresholds for maintaining some ecological services. Communities see their direct involvement and control of these tengefu as more likely to result in benefits flowing directly to them. Community closures are also important for articulating and resolving community values and strengthening their management capacity. Here, we describe the evolution of the tengefu movement in Kenya and combine information from focus group discussions, interviews, underwater surveys and boundary marking to evaluate the current status, opportunities and challenges facing these tengefu. We show that in some cases community closures suffer from slow and incomplete national and local legislative processes, challenges to compliance, and weak management.